(untitled) (Bangladesh Journal of Agriculture, 2024)
The experiment was conducted to evaluate the phenotypic expression and yield attributes of different pumpkin varieties in response to saline stress. The research work was carried out at Satkhira (AEZ-11) in the experimental field of Bangladesh Agricultural Research Institute, On-Farm Research Division, Khulna from 04 November 2020 to 28 February 2021 in Randomized Complete Block Design (RCBD) with four replications. The result indicated that the maximum vine length at harvest (330.1cm), number of leavesvine-1 (39.98), fresh weight of root (179.10 g), dry weight of root (14.92 g), fresh weight of shoot (499.80 g), dry weight of shoot (93.69 g), root length (11.82 cm), female flowervine-1 (2.25), number of fruitplant-1 (5.55), individual fruit weight (4230.00g), fruit yield (33.87 tha-1), flesh thickness (4.97 cm) were recorded from pumpkin var. BARI Misti Kumra-1 and number of node for 1st male flower (6.18), number of node for 1st female flower (29.29), total Soluble Solid (9.90) and β-carotene (110.15 µg/g) were recorded from BARI Misti Kumra-2. The fruit yields of the varieties ranged from19.36 to 33.87 tha-1. BARI Misti Kumra-1 might have the mechanism that is responsible for salt tolerance as well as will be useful for selection and improvement of Cucurbitaceous species. Bangladesh J. Agri. 2024, 49(1): 33-40